Food sources of fiber and micronutrients of concern among infants and young children in Lebanon: a national cross-sectional study - Fatima Al Zahraa Chokor; Nahla Hwalla; Farah Naja; Lara Nasreddine (BMC, 2024)
Abstract Background Intakes of fiber, iron, zinc, calcium, vitamin D, vitamin A, and folate were shown to be low in a substantial proportion of infants and children in Lebanon. The study aims to identify the top food sources of fiber, iron, zinc, calcium, vitamin D, vitamin A, and folate amongst infants and young children in Lebanon and to evaluate the evolution of food sources of these nutrients from the beginning of the complementary feeding journey up until the age of 47.9 months. Methods A national cross-sectional survey was conducted in 2012 as part of the "Early Life Nutrition and Health in Lebanon" project using stratified cluster sampling. Dietary intakes for infants and young children aged 6-47.9 months (n = 763) were assessed using 24- Hour Dietary Recall. Food items were categorized into food groups and the percent contribution of each food group to nutrient intakes was determined to identify the top food sources of fiber and selected micronutrients for three age groups: 6-11.9 m (infants), 12-23.9 m (toddlers), and 24-47.9 m (preschoolers). Results The top food source of fiber was vegetables among children aged 6-47.9 months. Among infants and toddlers, infant/young child formula was the main contributor to iron, zinc, calcium, vitamin D, vitamin A, and folate intakes. Baby cereals also contributed to around 14% of iron intakes among infants. Among preschoolers, meat and fish contributed to 13% of iron intakes and 29% of zinc intakes, while cow's milk was the major contributor of calcium (41%), vitamin D (81%) and vitamin A (25%) intakes. Sweetened beverages and sweet bakery were also ranked among the major food sources contributing to substantial intakes of key nutrients, including fiber, iron, zinc, calcium, vitamin A, and folate among infants, toddlers, and preschoolers. Conclusions In addition to milk sources, vegetables, beans and legumes, breads, meats, and rice and pasta, sweet bakery and sweetened beverages have contributed to intakes of key nutrients from early ages. This calls for implementing initiatives and designing approaches to support nutrition education and improve nutrient intakes in infancy and early childhood.